Gene Expression Profiling of the Paracrine Effects of Uterine Natural Killer Cells on Human Endometrial Epithelial Cells. (26th March 2014) - Gong, Xin; Chen, Zhenzhen; Liu, Yanxia; Lu, Qiudan; Jin, Zhe
Abstract : The endometrium contains a population of immune cells that undergo changes during implantation and pregnancy. The majority of these cells are uterine natural killer (uNK) cells; however, it is unclear how these cells interact with endometrial epithelial cells. Therefore, we investigated the paracrine effects of the uNK cell-secretion medium on the gene expression profile of endometrial epithelial cells in vitro through microarray analysis. Our results, which were verified by qRT-PCR and western blot, revealed that soluble factors from uNK cells alter the gene expression profiles of epithelial cells. The upregulated genes included interleukin-15 (IL-15) and interleukin-15 receptor alpha (IL-15RA), which result in a loop that stimulates uNK cell proliferation. In addition, vascular endothelial growth factor C (VEGF-C) and chemokine (C-X-C motif) ligand 10 (CXCL-10) were also determined to be upregulated in epithelial cells, which suggests that uNK cells work synergistically with epithelial cells to support implantation and pregnancy. In addition, oriental herbal medicines have been used to treat infertility since ancient times; however, we failed to find that Zi Dan Yin can regulate these endometrial paracrine effects.